Integration of torque controlled arm with velocity controlled base for mobile manipulation: An application to aircraft canopy polishing - Oetomo, Denny (Animo Repository, 2002)
A mobile manipulation system often involves combining more than one robot together, typically a manipulator arm and a mobile base. To implement force and motion control with dynamic compensation, a torque-controlled system is necessary. However, a torque-controlled robot is not always available. In fact, most commercially available mobile bases are velocity-controlled. This paper presents a method for combining a torque-controlled arm and a velocity-controlled base, while performing a force and motion task. The operational space formulation using a consistent set of integrated arm-base robot dynamics is employed in a mobile manipulation task of polishing an aircraft canopy. The torque controlled arm compensates for the dynamics introduced by the mobile base. The added mobility of the base enables the arm to cover the entire workspace.